2023
DOI: 10.2337/dc22-1710
|View full text |Cite
|
Sign up to set email alerts
|

Tirzepatide Reduces Appetite, Energy Intake, and Fat Mass in People With Type 2 Diabetes

Abstract: OBJECTIVE To evaluate the effects of tirzepatide on body composition, appetite, and energy intake to address the potential mechanisms involved in body weight loss with tirzepatide. RESEARCH DESIGN AND METHODS In a secondary analysis of a randomized, double-blind, parallel-arm study, the effects of tirzepatide 15 mg (N = 45), semaglutide 1 mg (N = 44), and placebo (N = 28) on body weight and composition, appetite, and energy i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 9 publications
(13 reference statements)
3
32
0
Order By: Relevance
“…Furthermore, 81%‐97% of participants achieved an HbA1c of less than 7.0% and 23%‐62% achieved an HbA1c of less than 5.7% 3–7 . In a mechanism‐of‐action study in people with T2D, tirzepatide was shown to improve glycaemic control by enhancing pancreatic beta‐cell function, improving insulin sensitivity and suppressing glucagon secretion, 8 as well as reducing food intake 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 81%‐97% of participants achieved an HbA1c of less than 7.0% and 23%‐62% achieved an HbA1c of less than 5.7% 3–7 . In a mechanism‐of‐action study in people with T2D, tirzepatide was shown to improve glycaemic control by enhancing pancreatic beta‐cell function, improving insulin sensitivity and suppressing glucagon secretion, 8 as well as reducing food intake 9 …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] In a mechanismof-action study in people with T2D, tirzepatide was shown to improve glycaemic control by enhancing pancreatic beta-cell function, improving insulin sensitivity and suppressing glucagon secretion, 8 as well as reducing food intake. 9 The robust glycaemic control observed with tirzepatide treatment in the phase 3 global registration trials (SURPASS-1 through SURPASS-5) was associated with clinically meaningful body weight reductions. [3][4][5][6][7] Study participants treated with tirzepatide lost on average 6-13 kg (7%-14%) of body weight.…”
mentioning
confidence: 99%
“…Tirzepatide is a single molecule that combines glucose-dependent insulinotropic polypeptide (GIP) and GLP-1 receptor agonism resulting in synergistic effects on appetite, food intake, and metabolic function . Tirzepatide is approved in many countries, including the US, EU, and Japan, as a once-weekly subcutaneous injectable for type 2 diabetes and for the treatment of obesity in the US and UK . In a placebo-controlled trial of participants with obesity or overweight without diabetes, tirzepatide led to mean reductions in body weight up to 20.9% after 72 weeks of treatment …”
Section: Introductionmentioning
confidence: 99%
“…The effects of diet-induced weight loss on nonfat body compartments has come into focus with two recent developments. First, new highly effective weight-loss agents for treating people with obesity are accompanied by relatively large changes in fat-free mass (FFM) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of diet‐induced weight loss on nonfat body compartments has come into focus with two recent developments. First, new highly effective weight‐loss agents for treating people with obesity are accompanied by relatively large changes in fat‐free mass (FFM) [5–8]. FFM includes the body's main functional tissues and organs, including SM, and excessive loss is viewed as an adverse pharmacologic effect [9–12].…”
Section: Introductionmentioning
confidence: 99%